Empowerment of the Jamu Gendong Kiringan Canden Community Based on Local Wisdom to Increase Literacy Embodied in Children's Literature - Siti Rochmiyati; Dinar Westri Andini; Didi Supriadi; Syamsul Hadi; Pardimin Pardimin; Imam Ghozali; Wahyu Setya Ratri; Agustinus Eko Susetyo; Muhammad Taufik Ismail; Charisma Wulan Widananda (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose The empowerment program will directly invite the Kiringan Canden herbal medicine community based on the local wisdom of traditional herbal medicine which is inherited from their ancestors to actively participate in increasing literacy and cultivating children's character which is embodied in children's literature. Methods - Methode community service activities. Result and discussions - The series of activities and results obtained prove that by collaborating with each other from all elements of society, especially involving the younger generation so that they have a good understanding of the local wisdom of the area, promoting behavior will emerge, understanding potential and in the end wanting to participate in preserving the ancestral heritage that has great potential to be appointed as a regional brand, so that the character values of nationalism, pride in local products, independence and mutual cooperation can be realized. Therefore, intermediaries or infrastructure are needed in order to pass on the order of life, tradition and culture to the next generation, so that there are no gaps between generations, so that community service programs by empowering herbal medicine communities based on local wisdom can increase literacy in maintain ancestral heritage. Presentation that is fun and in providing education to all residents, especially children, through explanation activities that are appropriate to the stage of child development, will facilitate and build literacy which has an impact on the formation of children's character. Conclusion - Empowerment by inviting the participation of all elements in society including the Jamu Gendong community, youth, children, men and women, community leaders and other residents to jointly preserve the ancestral heritage of "traditional herbal medicine" by directly empowering the Jamu Gendong community in increasing community-based literacy. local wisdom through fun activities, namely children's literature, is able to develop children's emotional intelligence and creativity, foster growth as well as children's personality and social skills. An interesting presentation will create fun and influence children so that indirectly they are able to cultivate the characters of respect, responsibility, caring, citizenship, honesty, cooperation, freedom, courage and justice so that in the future the children of this younger generation will continue and preserving the potential of the region.